The Building of a Single Information Space and the Elimination of Administrative Barriers under the Enlargement of the Eurasian Economic Union; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Bleikher O. V. Oksana Vladimirovna; Ageeva V. V. Vera Valentinovna; Fedorova T. N. Tamara Nikolaevna; Butorina N. B. Nataljya Borisovna; Brazovskaya O. E. Oksana Evgenjevna (2016, 2016)
Title screen